Photodegradation of Phenol under Visible Light Irradiation Using Cu-N-codoped ZrTiO4 Composite as a High-Performance Photocatalyst - Wanda Putra Fauzi; Rian Kurniawan; Sri Sudiono; Niko Prasetyo; Akhmad Syoufian (Indonesian Journal of Chemistry, 2024)
Codoping of nitrogen and copper into zirconium titanate composite (Cu-N-codoped ZrTiO4) was carried out through a sol-gel process. This study aimed to investigate the effect of copper and nitrogen dopants on the photocatalytic activity of ZrTiO4 composite in degrading phenol. To prepare the composite, an aqueous suspension of zirconia (ZrO2) alongside a fixed amount of urea and various amount of copper sulfate was added dropwise into diluted titanium(IV) tetraisopropoxide (TTIP) in ethanol. The composites were calcined at temperatures of 500, 700, and 900 °C. Fourier-transform infrared spectrophotometry (FTIR), X-ray diffraction (XRD), scanning electron microscopy with energy dispersive X-ray (SEM-EDX) mapping, and specular reflectance UV-visible spectrophotometry (SR UV-vis) were used for their characterization of composite. The photocatalytic activity was evaluated by adding the composite into a 10 mg L−1 phenol solution for various irradiation time spans. The remaining concentration of phenol solution was determined by absorption at 269 nm. Cu-N-codoped ZrTiO4 composite containing 5% Cu calcined at 500 °C demonstrated the highest observed rate constant and a significant band gap decrease from 3.13 to 2.68 eV.